KESANTUNAN BERBAHASA DALAM DISKUSI MAHASISWA DAN RELEVANSINYA TERHADAP PEMBELAJARAN PROFESI KEPENDIDIKAN DI FKIP UHN PEMATANGSIANTAR - Tarida Alvina Simanjuntak (IdeBahasa, 2019)
The objectives of this study are (1)to find out the realization of the principle of politeness in learning the Education Profession, and (2) to find out the principle of politeness that is dominantly used by students in discussions. The population in the study was all students who took the professional education courses in the German language education program and Christian religious education at the teaching learning fakulty Universitas HKBP Nommensen Pematangsiantar. The sample in this study is the entire population.This study used descriptive qualitative method. This research is a qualitative research that relies on phenomenology. This is because this research examines social phenomena (human actions) including the use of language.Data from the results of this study indicate that (1) The politeness principle used in the discussion activities in the teaching professional learning in Christianity education study programs and German language education there are 92 speeches. There are also 13 wisdom utterances, 2 generosity maxims, 3 praise utterances maxims, 1 speech modest maxim, 10 maxims of agreement, and 2 utterances of praise. Language politeness in discussions in the teaching profession is polite. Because most of them use polite speech in accordance with the principle of politeness.